Vital resonances encountering film with Varda, Haneke and Nancy - Hardy, Francesca Minnie (Edinburgh : Edinburgh University Press, 2021)
Establishes resonance as a critical and conceptual paradigm for film analysis bringing together, for the first time, the work of three of the leading figures in European film: Agnès Varda, Michael Haneke and Jean-Luc Nancy.
Frontmatter -- Contents -- Figures -- Acknowledgements -- Film, Resonance and the Senses -- Seeing with Oneself: Regarding Jean-Luc Nancy on Film -- La Pointe Courte: Avoid Contact with the Eyes and Skin, May Cause Irritation -- Time of the Wolf: Denatured Disaster Movie, Underwhelming Apocalypse, or the New Normal? -- Teenage Dreams in The Seventh Continent -- Le Bonheur: Happiness Made and Remade -- The Singular Plural of Seeing in Cleo from 5 to 7 -- Caché: If These Walls Could Talk -- Bad Resonance in The Piano Teacher -- Documenteur: A Resonant Picture -- Bloody Resonance -- Bibliography -- Index
Includes bibliographical references and index.
JSTOR
Keywords: Varda, Agnès, -- 1928-2019 -- Criticism and interpretation; Haneke, Michael, -- 1942- -- Criticism and interpretation; Nancy, Jean-Luc.; Haneke, Michael, -- 1942-; Nancy, Jean-Luc; Varda, Agnès, -- 1928-2019; Film criticism; Motion pictures -- Philosophy; Critique cinématographique.; Cinéma -- Philosophie; Film criticism; Motion pictures -- Philosophy; Criticism, interpretation, etc